EFL Students’ Perceptions of AI-Based Automated Self-Assessment in Academic Writing - Pratiwi, Ika Aditya; Yulia, Yuyun (LP. Ma'arif Janggan Magetan, 2025)
This study explores English as a Foreign Language (EFL) learners’ perceptions regarding the use of AI-based automated self-assessment tools and other writing technologies to improve grammatical accuracy and writing quality in English writing assignments. This study was conducted using qualitative methods. Data were collected through semi-structured interviews with five master’s students majoring in English education at Yogyakarta State University. They were selected by purposive sampling based on their experience using AI-based tools such as Grammarly and ProWritingAid. The data were then analyzed using thematic analysis, which involved several stages, including data recognition, initial coding, theme search, theme review, and theme definition and naming. This study shows that there are five challenges of using AI-based automated self-assessment tools. These are including context and interpretation errors, difficulty understanding feedback, dependence on paid features, lots of auto-feedback, and technology limitations. In the other hand, there are four benefits of using AI-based automated self-assessment. These are including increased self-confidence, efficiency in writing, independent learning, and better writing quality. This study contributes to the ongoing discussion about the role of technology in language learning, with a focus on how technology influences student learning outcomes, motivation, and reliance on automated feedback.